ANTIOXIDANT ACTIVITY, TOTAL PHENOL, AND FLAVONOID CONTENT EXTRACTS AND FRACTIONS MANGO SEEDS (Mangifera indica L.) - Anjani, Ratna; Kasmawati, Henny; Yamin; Salamah, Nina (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Antioxidants can either stop or slow down the excessive oxidation of a compound. This study aimed to determine the secondary metabolite compounds, antioxidant activity, total flavonoid and phenolic levels, and the correlation between the levels of flavonoid and phenolic compounds in inhibiting free radicals. The DPPH (1,1-diphenyl-2-picrylhydrazyl) method was used to evaluate antioxidant activity. Determination of total flavonoid levels using a UV-Vis spectrophotometer and the aluminum chloride method. The total phenolic content was determined using the Folin-Ciocalteu method. Based on the results of phytochemical screening, mango seed extract (Mangifera indica L.) contains secondary metabolites such as alkaloids, flavonoids, terpenoids, phenolics, and tannins. The relationship between the antioxidant activity of the DPPH method and total flavonoid levels was 91.31%, respectively. The relationship between the antioxidant activity of the DPPH method and the total phenolic content was 99.64%. Keywords: Mangifera indica L, secondary metabolites, antioxidant activity, DPPH, total flavonoids, total phenolics.